Factors Associated with the Nutritional Status of Pregnant Women in the Coastal Area of Telaga Dewa Health Center, Bengkulu City - Heli Nurcahyanti Hulmia; Fery Surahman; Retni Retni (Student Scientific Journal, 2026)
Background: The nutritional status of pregnant women is a key determinant of maternal health and fetal development, particularly in socioeconomically vulnerable coastal areas. Telaga Dewa Health Center recorded the highest prevalence of Chronic Energy Deficiency (CED) among pregnant women in Bengkulu City in 2023, with 111 cases, and 73 cases were still found in 2024. Objective: This study aimed to identify the factors associated with the nutritional status of pregnant women in the coastal area. Methods: A cross-sectional design was employed involving 71 pregnant women selected through random sampling. The independent variables were nutritional knowledge, dietary patterns, and family income, while the dependent variable was nutritional status measured using Mid-Upper Arm Circumference (MUAC). Data were analyzed using univariate and bivariate methods with the Chi-Square test at a 0.05 significance level. Result: The results showed that 40.8% of respondents had low nutritional knowledge, 57.7% had unbalanced dietary patterns, 63.4% had family incomes ≤ IDR 2,930,669, and 38.0% were undernourished. Significant associations were found between nutritional status and nutritional knowledge (p = 0.002), dietary patterns (p = 0.015), and family income (p = 0.026). Cobclusion: This study concludes that improving nutritional knowledge, promoting balanced dietary practices, and strengthening family economic capacity are essential to enhancing the nutritional status of pregnant women in coastal communities.